Comparison of the results of aerobic loading diagnostic while kayaking in counter-current pool and while arm crank ergometry - Busta, J.; Bilý, M. (Journal of Outdoor Activities, 2014)
The aim of this study was to realize an aerobic loading test while kayaking in the counter-current pool and detect the cardiorespiratory endurance level of Czech elite slalom racers. The research group consisted of 8 professional kayakers. The results detected while paddling on kayak [VO2max (ml/kg): 38.49 (7.82); HR (/min): 181.88 (4.99), RR (min-1) 36.63 (6.56); O2 pulse/kg (ml): 0.21 (0.04), VMAX (l/min): 103.03 (10.14)] were compared to the results detected while arm crank ergometry [VO2max (ml/kg): 66.27 (3.16); HR (/min): 183.0 (6.02), RR (/min) 65.38 (4.27); O2pulse/kg (ml): 0.36 (0.02), Vmax (l/min): 142.14 (13.50)]. Paddling kayakers reached on average about 31.13% (16.35) lower values than while arm crank ergometry although in 4 of total 5 resulting values of chosen functional indicators were made out medium to high measure of interdependence (r=0.623-0.777) between mentioned tests. Assumption of significant similarity rate of measured functional values was established merely at HR (/min). With regard to probands feed-back, the differences between tests are primarily explained by the need for use plastic kayak and braking device due to inadequate speed and proportional parameters of the pool. These arrangements might have changed the experimental conditions so much that they led to the local exhaustion of upper limbs whilst cardiorespiratory potential of competitors did not reach its maximum.